Automated College Bell System: Integrating Arduino and Real-Time Clock - Bhandare, Prashant; Suresh, Chavan Atharv; Vilas, More Tejas (International Journal of Computer Sciences and Engineering, 2024)
The Automated College Bell System (ACBS) is a system Which is used to manage the academic schedules. This system automates the ringing of bells at designated intervals, aligning with class schedules and campus events. The system features a robust notification mechanism, ensuring that students and faculty receive real-time alerts about changes in the schedule, special events, or emergencies. Additionally, the ACBS can be synchronized with academic calendars, providing flexibility and adaptability to varying schedules throughout the semester. Implementation of the ACBS not only improves punctuality and time management within the college environment but also reduces reliance on physical resources, contributing to a more eco-friendly campus. Future developments may include advanced features such as voice alerts and integration with smart campus technologies.